Challenges and advancements in the development of vaccines and therapies against Chagas disease - Pinazo, Maria Jesus (2024)
Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, presents a substantial global health burden, affecting millions of individuals worldwide and posing a continual risk of infection. Despite the high mortality and morbidity rates, effective vaccines to prevent infection by the parasite remain elusive, and the drugs currently available are suboptimal. Understanding the intricate dynamics of parasite–host interactions and the resulting immune responses, which contribute to both protection and pathology, is crucial for the development of effective vaccines and therapies against Chagas disease. In this Series paper, we discuss the challenges associated with discovering and translating prophylactic and therapeutic strategies from the laboratory bench to clinical application. We highlight ongoing efforts in vaccine and new drug development, with a focus on more advanced candidates for vaccines and drugs. We also discuss potential solutions, emphasising the importance of collaborative research efforts, sustained funding, and a comprehensive understanding of host–parasite interactions and immunopathology to advance the development of new vaccines and therapies against Chagas disease.